TRANSFORMASI PEMBELAJARAN PAI MELALUI TEORI KONSTRUKTIVISTIK DI SEKOLAH DASAR ISLAM TERPADU UMMI KOTA BENGKULU - Siti Handika; Nurlaili (Institut Agama Islam Hamzanwadi NW Lombok Timur, 2025)
Islamic Religious Education (IRE) at SDIT Ummi Kota Bengkulu applies a constructivist approach to shape the religious character of students. This approach emphasizes the active role of students in building knowledge through direct experience and social interaction. This study aims to examine the implementation of constructivist theory in IRE learning, as well as the supporting and inhibiting factors in forming students' religious character. A qualitative descriptive method was employed, using data collection techniques such as observation, in-depth interviews, and documentation study. The findings indicate that the implementation of constructivist theory is effective, with active learning methods such as discussions, problem-solving, and religious projects. Additionally, parental involvement through the